Austenitic stainless steel

By optimizing the composition of austenitic stainless steel with a controlled surface oxide of Cr, Si, and Al, the steel achieves excellent red scale resistance and low manufacturing costs, addressing the challenges faced by existing technologies.

JP7656463B2Active Publication Date: 2025-04-03NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021058551
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-04-03
Estimated Expiration
2041-03-30

AI Technical Summary

Technical Problem

Existing austenitic stainless steels face challenges in achieving excellent red scale resistance while maintaining low manufacturing costs, as methods to enhance red scale resistance often increase costs due to additional elements or processes.

Method used

The development of an austenitic stainless steel with a specific composition, including C: 0.12% or less, Si: 0.20-4.0%, and a surface oxide containing Cr, Si, and Al with a long diameter of 0.1 to 5 μm, which provides enhanced red scale resistance without the need for costly surface polishing or additional manufacturing steps.

Benefits of technology

This approach results in an austenitic stainless steel that achieves excellent red scale resistance while maintaining low manufacturing costs, as the controlled oxide composition acts as a protective coating, reducing the formation of red scale and improving high-temperature strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656463000003
    Figure 0007656463000003
  • Figure 0007656463000001
    Figure 0007656463000001
  • Figure 0007656463000002
    Figure 0007656463000002
Patent Text Reader

Abstract

To provide austenitic stainless steel that can be manufactured at a low cost and has excellent red scale resistance.SOLUTION: The austenitic stainless steel includes, by mass, 0.12% or less C, 0.20 to 4.0% Si, 0.05 to 2.5% Mn, 0.05% or less P, 0.005% or less S, 8.0 to 17.0% Ni, 15 to 25.0% Cr, 2.5% or less Cu, 0.01 to 1.0% Al, 0.35% or less N, 3.0% or less Mo, 0.8% or less Nb, 1.0% or less Ti, and the balance Fe with inevitable impurities. An oxide containing Cr, Si and Al is formed on a surface thereof. In the oxide, a total amount of a concentration of Cr and a concentration of at least one of Si and Al is 4.0 to 12.0 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an austenitic stainless steel having excellent resistance to red scale. [Background technology]

[0002] When austenitic stainless steel is used for applications such as exhaust gas passage components, stove combustion, fuel cell components, etc., it is usually heated to high temperatures of 300 to 900°C during use. Furthermore, in the above applications, the austenitic stainless steel is used in an environment containing water vapor, which can cause red scale, which is an Fe-based oxide, to form on the surface.

[0003] The red scale formed may scatter and adhere to other parts, causing adverse effects, and may also reduce high-temperature strength due to thinning caused by oxidation. Therefore, austenitic stainless steels that have red-scale resistance in a high-temperature steam atmosphere are desired. Various methods have been known to improve high red-scale resistance.

[0004] Patent Document 1 discloses an austenitic stainless steel material with excellent red scale resistance, which is obtained by adjusting the total amount of Si and Al contained therein and performing mechanical polishing finishing. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2004-043903 A Summary of the Invention [Problem to be solved by the invention]

[0006] According to the technology described in Patent Document 1, red scale can be prevented by promoting Cr diffusion in steel. However, in order to improve red scale resistance using such conventional technology, the amount of added elements must be increased or a manufacturing process must be added, resulting in increased manufacturing costs.

[0007] An object of one aspect of the present invention is to provide an austenitic stainless steel that can be produced at low cost and has excellent red scale resistance. [Means for solving the problem]

[0008] In order to solve the above problems, an austenitic stainless steel according to one embodiment of the present invention contains, by mass%, C: 0.12% or less, Si: 0.20 to 4.0%, Mn: 0.05 to 2.5%, P: 0.05% or less, S: 0.005% or less, Ni: 8.0 to 17.0%, Cr: 15 to 25.0%, Cu: 2.5% or less, Al: 0.01 to 1.0%, N: 0.35% or less, Mo: 3.0% or less, Nb: 0.8% or less, and Ti: 1.0% or less, with the balance being Fe and unavoidable impurities, and has an oxide containing Cr, Si and Al and having a major axis of 0.1 to 5 μm formed on the surface, and in the oxide, the sum of the concentration of Cr and the concentration of at least one of Si and Al is 4.0 to 12.0% by mass.

[0009] In the austenitic stainless steel according to one aspect of the present invention, the oxide may have a total concentration of Cr, Si, and Al of 5.0 to 12.0 mass %.

[0010] An austenitic stainless steel according to one embodiment of the present invention may further contain, by mass%, one or more of B: 0.01% or less, Ca: 0.0002 to 0.0050%, Hf: 0.001 to 0.50%, Zr: 0.01 to 0.50%, Sb: 0.005 to 0.50%, Co: 0.01 to 1.50%, W: 0.01 to 2.0%, Ta: 0.001 to 1.0%, Sn: 0.002 to 0.5%, Ga: 0.0002 to 0.30%, Mg: 0.0003 to 0.0050%, and rare earth elements: 0.001 to 0.20%. Effect of the Invention

[0011] According to one aspect of the present invention, it is possible to realize an austenitic stainless steel that can be manufactured at low cost and has excellent red scale resistance. [Brief description of the drawings]

[0012] [Figure 1] 1 is a flowchart showing an example of a method for producing an austenitic stainless steel according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] An embodiment of the present invention will be described below. The following description is provided for better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified. In this specification, "A to B" indicates A or more and B or less. In this specification, the term "stainless steel" refers to a stainless steel material whose specific shape is not limited. Examples of this stainless steel material include steel plates, steel pipes, and bar steel.

[0014] <Composition of austenitic stainless steel> The composition of components contained in an austenitic stainless steel according to one embodiment of the present invention is as follows.

[0015] An austenitic stainless steel according to one embodiment contains, by mass%, C: 0.12% or less, Si: 0.20-4.0%, Mn: 0.05-2.5%, P: 0.05% or less, S: 0.005% or less, Ni: 8.0-17.0%, Cr: 15-25.0%, Cu: 2.5% or less, Al: 0.01-1.0%, N: 0.35% or less, Mo: 3.0% or less, Nb: 0.8% or less, and Ti: 1.0% or less. In addition to the components shown below, the austenitic stainless steel is made of iron (Fe) or small amounts of impurities that are inevitably mixed in (unavoidable impurities).

[0016] (Carbon:C) C is an austenite-forming element that stabilizes the austenite phase and is effective in maintaining non-magnetic properties. C is also an element that is effective in solid solution strengthening of the austenite phase. However, if C is contained in excess, the amount of carbides increases and corrosion resistance decreases. Therefore, in the austenitic stainless steel according to one embodiment, the C content is 0.12 mass% or less, and preferably 0.005 to 0.08 mass%.

[0017] (Silicon: Si) Silicon is an element effective in improving red scale resistance. However, excessive silicon content can cause deterioration in toughness and workability. Therefore, in the austenitic stainless steel according to one embodiment, the silicon content is 0.20 to 4.0 mass%, and preferably 0.30 to 3.5 mass%.

[0018] (Manganese: Mn) Mn is an austenite-forming element in austenitic stainless steel and improves the adhesion of scale. However, excessive Mn content promotes the generation of MnS, which is the starting point of corrosion. Therefore, in the austenitic stainless steel according to one embodiment, the Mn content is 0.05 to 2.5 mass%, and preferably 0.1 to 2.0 mass%.

[0019] (Rin:P) Workability decreases if P is contained in excessive amount, therefore, in the austenitic stainless steel according to one embodiment, the P content is 0.05 mass % or less, preferably 0.01 to 0.04 mass %.

[0020] (Sulfur: S) Excessive S content promotes the formation of corrosion starting points in austenitic stainless steel, so the S content in the austenitic stainless steel according to one embodiment is 0.005 mass% or less, and preferably 0.0001 to 0.002 mass%.

[0021] (Nickel: Ni) Ni is an element that improves the corrosion resistance of austenitic stainless steel. However, excessive Ni content increases material costs. Therefore, in the austenitic stainless steel according to one embodiment, the Ni content is 8.0 to 17.0 mass%, and preferably 9.0 to 15.0 mass%.

[0022] (Chromium: Cr) Cr is an essential element for forming a passive film and ensuring corrosion resistance. It is also effective for ensuring red scale resistance. However, excessive Cr content increases material costs and causes a decrease in toughness. Therefore, in an austenitic stainless steel according to one embodiment, the Cr content is 15.0 to 25.0 mass%, and preferably 17.0 to 21.0 mass%.

[0023] (Copper: Cu) Cu is an element added to ensure high-temperature strength. However, excessive Cu content increases material costs. Therefore, in the austenitic stainless steel according to one embodiment, the Cu content is 2.5 mass% or less, and preferably 0.02 to 2.2 mass%.

[0024] (Aluminum: Al) Al is an element effective for improving the corrosion resistance of austenitic stainless steel and for improving red scale resistance. Also, Al is an element effective as a deoxidizer during steelmaking. However, if Al is contained excessively, there is a possibility that the surface quality will deteriorate. Therefore, in the austenitic stainless steel according to one embodiment, the content of Al is 0.01 to 1.0 mass%, and preferably 0.02 to 0.10 mass%.

[0025] (Nitrogen: N) N is an austenite-forming element and is effective in maintaining non-magnetic properties. However, excessive N content will form nitrides with other elements, leading to hardening. Therefore, in the austenitic stainless steel according to one embodiment, the N content is 0.35 mass% or less, and preferably 0.005 to 0.30 mass%.

[0026] (Molybdenum: Mo) Mo is an element added to ensure high-temperature strength and red scale resistance. However, excessive Mo content hardens the material, reduces workability, and increases material costs. Therefore, in the austenitic stainless steel according to one embodiment, the Mo content is 3.0 mass% or less, and preferably 0.01 to 2.5 mass%.

[0027] (Niobium: Nb) Nb is an element added to ensure high-temperature strength. However, excessive Nb content can deteriorate workability and toughness. Therefore, in the austenitic stainless steel according to one embodiment, the Nb content is 0.8 mass% or less, and preferably 0.01 to 0.5 mass%.

[0028] (Titanium: Ti) Ti is an element that improves red scale resistance and workability. However, excessive Ti content may deteriorate workability and surface quality. Therefore, in the austenitic stainless steel according to one embodiment, the Ti content is 1.0 mass% or less, and preferably 0.01 to 0.5 mass%.

[0029] <Other ingredients> An austenitic stainless steel according to one embodiment of the present invention may further contain, by mass%, one or more of B: 0.01% or less, Ca: 0.0002 to 0.0050%, Hf: 0.001 to 0.50%, Zr: 0.01 to 0.50%, Sb: 0.005 to 0.50%, Co: 0.01 to 1.50%, W: 0.01 to 2.0%, Ta: 0.001 to 1.0%, Sn: 0.002 to 0.5%, Ga: 0.0002 to 0.30%, Mg: 0.0003 to 0.0050%, and rare earth elements: 0.001 to 0.20%.

[0030] (Boron: B) B is an element that improves the secondary workability of a molded product manufactured using austenitic stainless steel. However, if B is contained in excess, compounds such as Cr2B are likely to be formed, which may deteriorate the red scale resistance. Therefore, in the austenitic stainless steel according to one embodiment, 0.01 mass % or less of B may be added as necessary, and preferably 0.0001 to 0.0030 mass % of B may be added.

[0031] (Calcium: Ca) Ca is an element that promotes high-temperature oxidation resistance. However, excessive addition of Ca leads to a decrease in corrosion resistance. Therefore, in the austenitic stainless steel according to one embodiment, 0.0002 to 0.0050 mass % of Ca may be added as necessary, and preferably 0.0003 to 0.0040 mass % of Ca may be added.

[0032] (Hafnium: Hf) Hf is an element that improves corrosion resistance, high-temperature strength, and oxidation resistance. However, excessive addition of Hf may lead to deterioration of workability and manufacturability. Therefore, in the austenitic stainless steel according to one embodiment, 0.001 to 0.50 mass % of Hf may be added as necessary, and preferably 0.005 to 0.10 mass % of Hf may be added.

[0033] (Zirconium: Zr) Zr is an element that improves high-temperature strength, corrosion resistance, and high-temperature oxidation resistance. However, excessive addition of Zr leads to deterioration of workability and manufacturability. Therefore, in the austenitic stainless steel according to one embodiment, 0.01 to 0.50 mass % of Zr may be added as necessary, and preferably 0.02 to 0.30 mass % of Zr may be added.

[0034] (Antimony: Sb) Sb is an element that improves high-temperature strength. However, excessive addition of Sb reduces weldability and toughness. Therefore, in the austenitic stainless steel according to one embodiment, 0.005 to 0.50 mass % of Sb may be added as necessary, and preferably 0.010 to 0.25 mass % of Sb may be added.

[0035] (Cobalt: Co) Co is an element that improves high-temperature strength. However, excessive addition of Co leads to a decrease in toughness and therefore to a decrease in manufacturability. Therefore, in the austenitic stainless steel according to one embodiment of the present invention, 0.01 to 1.50 mass % of Co may be added as necessary, and preferably 0.03 to 1.0 mass % of Co may be added.

[0036] (Tungsten: W) W is an element added to ensure high-temperature strength. However, excessive W content increases material costs. Therefore, in the austenitic stainless steel according to one embodiment, 0.01 to 2.0 mass % of W may be added as necessary, and preferably 0.03 to 1.50 mass % of W may be added.

[0037] (Tantalum: Ta) Ta is an element that improves high-temperature strength. However, excessive addition of Ta reduces weldability and toughness. Therefore, in the austenitic stainless steel according to one embodiment, 0.001 to 1.0 mass % of Ta may be added as necessary, and preferably 0.010 to 0.50 mass % of Ta may be added.

[0038] (Tin: Sn) Sn is an element that improves corrosion resistance and high-temperature strength. However, excessive addition of Sn may lead to a decrease in toughness and manufacturability. Therefore, in the austenitic stainless steel according to one embodiment, 0.002 to 0.50 mass % of Sn may be added as necessary, and preferably 0.005 to 0.20 mass % of Sn may be added.

[0039] (Gallium: Ga) Ga is an element that improves corrosion resistance and hydrogen embrittlement resistance. However, excessive addition of Ga reduces weldability and toughness. Therefore, in the austenitic stainless steel according to one embodiment, 0.0002 to 0.30 mass % of Ga may be added as necessary, and preferably 0.0010 to 0.20 mass % of Ga may be added.

[0040] (Magnesium: Mg) Mg is a deoxidizing element and also an element that refines the structure of the slab and improves formability. However, excessive addition of Mg leads to deterioration of corrosion resistance, weldability, and surface quality. Therefore, in the austenitic stainless steel according to one embodiment, 0.0003 to 0.0050 mass% of Mg may be added as necessary, and preferably 0.0005 to 0.0030 mass% of Mg may be added.

[0041] (Rare earth elements: REM) REM refers to a collective term for scandium (Sc), yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). REM may be added as a single element or as a mixture of multiple elements. REM is an element that improves the cleanliness of stainless steel and also improves high-temperature oxidation resistance. However, excessive addition increases the alloy cost and reduces manufacturability. Therefore, in the austenitic stainless steel according to one embodiment, 0.001 to 0.20 mass % of REM may be added as necessary, and preferably 0.005 to 0.10 mass % of REM may be added.

[0042] <Oxide containing Cr, Al and Si> In the austenitic stainless steel according to one embodiment of the present invention, on the surface, there are oxides containing Cr, Al and Si with a major axis of 0.1 to 5 μm. In this specification, such oxides present on the surface of the austenitic stainless steel may be referred to as "the oxides of the present invention".

[0043] The major axis of the oxide refers to the maximum distance among the distances between any two points on the oxide surface. The oxides of the present invention exhibit an improved effect on red scale resistance if the major axis is 0.1 to 5 μm. When the major axis of the oxides of the present invention is less than 0.1 μm, the improvement effect on red scale resistance by the oxides of the present invention is low. Also, when the major axis of the oxides of the present invention is greater than 5 μm, a Cr-depleted layer is likely to be formed, and the surface design property of the austenitic stainless steel also deteriorates. The Cr-depleted layer will be described later.

[0044] In the austenitic stainless steel according to one embodiment, on the surface, oxides containing Cr, Si and Al with a major axis of 0.1 to 5 μm are formed, and in the said oxides, the total of the concentration of Cr and the concentration of at least one of Si and Al is 4.0 to 12.0 mass%.

[0045] On the surface of the austenitic stainless steel, the oxides of the present invention on the surface of the austenitic stainless steel can be detected and analyzed, for example, by a Scanning Electron Microscope (SEM). Also, the content of Cr, Al or Si in the oxides on the surface of the austenitic stainless steel can be measured, for example, by an Energy dispersive X-ray spectroscopy (EDS).

[0046] The reasons why the oxide of the present invention improves red scale resistance are believed to be as follows. First, the oxide of the present invention acts as a protective coating. Second, the oxide of the present invention grows by heating, and the oxygen partial pressure around the oxide of the present invention decreases. Since Al, Si, Cr, and Fe are more likely to be oxidized in that order, Al, Si, and Cr are oxidized preferentially over Fe. Therefore, the growth of the oxide of the present invention reduces the formation of red scale, which is an Fe-based oxide, and the formation of oxides with excellent protective properties mainly composed of Cr, Al, and Si (e.g., Cr2O3) becomes more preferential.

[0047] However, when the total of the Cr concentration, Al concentration and / or Si concentration in the oxide of the present invention present on the surface of the austenitic stainless steel is excessive, firstly, a Cr-poor layer containing less Cr is formed on the surface. This is because, unless pickling is performed under appropriate conditions after the final annealing process of the austenitic stainless steel, a Cr-poor layer (on the parent phase side) remains at the interface between the oxide formed on the surface and the parent phase. In this case, Fe-based oxides tend to remain on the surface of the austenitic stainless steel even after the nitric hydrofluoric acid immersion process, and the red scale resistance is reduced. Secondly, there is a risk that the weldability of the austenitic stainless steel is reduced due to the oxide of the present invention. Therefore, the total of the Cr concentration, Al concentration and / or Si concentration in the oxide of the present invention on the surface of the austenitic stainless steel is preferably 12.0 mass% or less.

[0048] If the total of the Cr concentration, Al concentration and / or Si concentration of the oxide of the present invention on the surface of the austenitic stainless steel is less than 4.0 mass%, the effect of improving red scale resistance by the oxide of the present invention is insufficient. Therefore, it is preferable to control the total of the Cr concentration, Al concentration and / or Si concentration of the oxide of the present invention on the surface of the austenitic stainless steel within the range of 4.0 to 12.0 mass%.

[0049] Furthermore, it is more preferable that the total concentration of Cr, Al and Si on the surface of the austenitic stainless steel is 5.0 to 12.0 mass %.

[0050] Conventionally, the general approach to improving red scale resistance was to increase the amount of Cr and Si added or to increase the number of manufacturing steps (surface polishing, pre-oxidation, etc.), which resulted in increased manufacturing costs. The present inventors focused on oxides containing Cr, Al, and Si on the surface of austenitic stainless steel. They then discovered that by controlling the concentrations of Cr, Al, and Si contained in such oxides on the surface of austenitic stainless steel within a predetermined range, it is possible to realize an austenitic stainless steel with excellent red scale resistance.

[0051] The present inventors have found that, for example, by the following manufacturing method, it is possible to obtain an austenitic stainless steel having excellent red scale resistance in which the total of the Cr concentration, Al concentration and / or Si concentration of the oxide of the present invention on the surface is 4.0 to 12.0 mass %.

[0052] <Method of manufacturing austenitic stainless steel> The austenitic stainless steel according to one embodiment of the present invention is obtained, for example, as an austenitic stainless steel strip. Fig. 1 is a flow chart showing an example of a method for producing an austenitic stainless steel according to one embodiment. As shown in Fig. 1, the method for producing an austenitic stainless steel strip according to this embodiment includes a pretreatment step S1, a hot rolling step S2, an annealing step S3, a pickling step S4, a cold rolling step S5, a final annealing step S6, a sulfuric acid immersion step S7, a nitric acid electrolysis step S8, and a nitric hydrofluoric acid immersion step S9.

[0053] In the pretreatment step S1, first, a melting furnace in a vacuum or argon atmosphere is used to melt steel having a composition adjusted to fall within the range of the present invention, and the steel is cast to produce a slab (steel ingot). Then, a slab piece for hot rolling is cut out from the slab. The slab piece is then heated to a temperature range of 1100 to 1300°C in an air atmosphere. The time for which the slab piece is heated and held is not limited. When the pretreatment step is carried out industrially, the casting may be continuous casting.

[0054] The hot rolling step S2 is a step of producing a hot rolled steel strip having a predetermined thickness by hot rolling the slab obtained in the pretreatment step S1.

[0055] The annealing step S3 is a step for softening the hot-rolled steel strip obtained in the hot rolling step S2 by heating the steel strip. The annealing step S3 is a step that is performed as necessary, and does not necessarily have to be performed.

[0056] The pickling step S4 is a step of washing off scale adhering to the surface of the steel strip using a pickling solution such as hydrochloric acid or a mixture of nitric acid and hydrofluoric acid.

[0057] The cold rolling step S5 is a step in which the steel strip that has been descaled in the pickling step S4 is further rolled to a thinner thickness.

[0058] The final annealing step S6 is a step in which the steel strip rolled in the cold rolling step S5 is heated to remove distortion and soften the steel strip. The annealing in the final annealing step S6 is performed at a temperature of 1000 to 1100° C. depending on the alloy components.

[0059] The sulfuric acid immersion step S7, the nitric acid electrolysis step S8, and the nitric hydrofluoric acid immersion step S9 are steps for leaving the oxide of the present invention on the surface of the manufactured austenitic stainless steel. In other words, the sulfuric acid immersion step S7, the nitric acid electrolysis step S8, and the nitric hydrofluoric acid immersion step S9 can also be called surface oxide remaining steps.

[0060] The sulfuric acid immersion step S7 is a step of immersing the steel strip obtained in the final annealing step S6 in an aqueous sulfuric acid solution. The sulfuric acid concentration of the aqueous sulfuric acid solution in the sulfuric acid immersion step S7 is preferably 50 g / L or more, more preferably 60 g / L or more, and even more preferably 70 g / L or more. The liquid temperature of the aqueous sulfuric acid solution in the sulfuric acid immersion step S7 is preferably 40°C or more, and even more preferably 50°C or more. The immersion time of the steel strip in the aqueous sulfuric acid solution in the sulfuric acid immersion step S7 is preferably 20 to 50 seconds, and even more preferably 25 to 35 seconds.

[0061] The nitric acid electrolysis step S8 is a step in which the steel strip after the sulfuric acid immersion step S7 is electrolyzed in an aqueous nitric acid solution. The nitric acid concentration of the aqueous nitric acid solution in the nitric acid electrolysis step S8 is preferably 130 g / L or more, and more preferably 150 g / L or more. The liquid temperature of the aqueous nitric acid solution in the nitric acid electrolysis step S8 is preferably 40 to 60°C. The current density in the nitric acid electrolysis step S8 is 50 mA / cm 2 It is preferable that the current is 70mA / cm or more. 2 It is more preferable that the electrolysis time in the nitric acid electrolysis step S8 is 60 seconds or more. The upper limits of the nitric acid concentration, current density, and electrolysis time in the nitric acid electrolysis step S8 are not particularly limited, but the nitric acid concentration is preferably 250 g / L or less, and the current density is preferably 150 mA / cm. 2 In the following, the electrolysis time is preferably 180 seconds or less.

[0062] The nitric hydrofluoric acid immersion step S9 is a step of immersing the steel strip after the nitric acid electrolysis step S8 in a nitric hydrofluoric acid aqueous solution which is a mixed solution of an aqueous nitric acid solution and an aqueous hydrofluoric acid solution. The nitric acid concentration of the nitric hydrofluoric acid aqueous solution in the nitric hydrofluoric acid immersion step S9 is preferably 130 to 150 g / L, and the hydrofluoric acid concentration is preferably 10 to 15 g / L. The liquid temperature of the nitric hydrofluoric acid aqueous solution in the nitric hydrofluoric acid immersion step S9 is preferably 40 to 60° C. The immersion time of the steel strip in the nitric hydrofluoric acid aqueous solution in the nitric hydrofluoric acid immersion step S9 depends on the component composition of the austenitic stainless steel, but is preferably 40 to 60 seconds.

[0063] The present inventors have found that the above-mentioned production method makes it possible to leave the oxide of the present invention, which has a major axis of 0.1 to 5 μm and contains Cr, Si and Al, on the surface of austenitic stainless steel.

[0064] Furthermore, in the austenitic stainless steel according to one embodiment of the present invention, the total concentration of Cr and at least one of Si and Al contained in the oxide of the present invention formed on the surface is 4.0 to 12.0 mass %. As a result, the austenitic stainless steel according to one embodiment does not require treatment such as surface polishing to improve red scale resistance, and can be produced at low cost. EXAMPLES

[0065] An embodiment of the present invention will be described below. As inventive or comparative examples of austenitic stainless steel, steel materials No. 1 to 56 were produced as follows. First, the components shown in Table 1 below were used as raw materials, and the above-mentioned manufacturing method was carried out up to the final annealing step S6 under the following conditions: Atmosphere of the melting furnace in the pretreatment process S1: Vacuum Mass of slab piece produced in pre-treatment process S1: 30 kg Heating temperature of slab in pretreatment process S1: 1230℃ Heating time of the slab in pretreatment step S1: 2 hours -Thickness after hot rolling process S2: 5mm Annealing process S3: Not performed Pickling solution used in pickling process S4: Nitric hydrofluoric acid solution (3% hydrofluoric acid, 10% nitric acid) - Temperature of pickling solution in pickling process S4: 60℃ -Thickness after cold rolling process S5: 2mm Annealing temperature in the final annealing step S6: 1000 to 1100°C (varies depending on the alloy composition).

[0066] In this example, the compositions shown in Table 1 are shown in mass%. The balance other than each component shown in Table 1 is Fe or a small amount of impurities that are inevitably mixed in. The underlines in Table 1 indicate that the range of each component contained in each stainless steel according to the comparative example of the present invention is outside the range of the present invention.

[0067] Next, in order to leave the oxide of the present invention on the surface of the steel strip, a sulfuric acid immersion step S7, a nitric acid electrolysis step S8, and a nitric hydrofluoric acid immersion step S9 were carried out under the following conditions: Sulfuric acid concentration in sulfuric acid immersion process S7: 80g / L - Sulfuric acid temperature in the sulfuric acid immersion process S7: 60℃ Nitric acid concentration in nitric acid electrolysis process S8: 200g / L Nitric acid liquid temperature in nitric acid electrolysis process S8: 40-60℃ Current density in nitric acid electrolysis step S8: 80mA / cm 2 Nitric acid aqueous solution used in the nitric acid soaking process S9: nitric acid 130-150g / L, hydrofluoric acid 10-15g / L Nitric hydrofluoric acid liquid temperature in the nitric hydrofluoric acid immersion process S9: 40 to 60°C.

[0068] The immersion time in sulfuric acid in the sulfuric acid immersion step S7 was 30 seconds. The electrolysis time in the nitric acid electrolysis step S8 was 60 seconds. The immersion time in the nitric hydrofluoric acid aqueous solution in the nitric hydrofluoric acid immersion step S9 was 60 seconds. The hydrofluoric acid concentration (g / L) in the nitric hydrofluoric acid immersion step S9 for each steel material is shown in Table 2.

[0069] [Table 1]

[0070] [Table 2]

[0071] For steel materials Nos. 1 to 56, the concentrations of Cr, Al, and Si contained in the oxide on the steel material surface were measured, and the oxidation weight gain and weldability were evaluated by the methods described below.

[0072] <Oxide concentration measurement> The analysis of Cr, Si, and Al-based oxides on the surface of each steel material was carried out as follows. A scanning electron microscope (SEM) SU5000 (Hitachi High-Technologies Corporation) was used to analyze the oxides dispersed on the steel surface at a magnification of 10,000 times. In addition, elemental analysis of the oxide composition was carried out using an energy dispersive X-ray spectroscopy (EDS) for electron microscopes (Horiba, Ltd.) at an acceleration voltage of 15 kV, an analysis time of 60 seconds, and a beam diameter of 0.2 μm.

[0073] The area analyzed was 6μm×4μm=24μm 2 The oxide size measured was within the range of 0.1 to 5 μm in major axis. On the surface of each steel material, there were 10 or more oxides of this size, and the maximum diameter was 24 μm. 2 The analysis range was the area within the range of 0.1 to 5 μm. Five locations were randomly selected from within the analysis range that contained oxides with a major axis of 0.1 to 5 μm, and spot analysis was performed by EDS with the target elements being Fe, Ni, Cr, Si, Al, and O. The analysis results for each steel material were calculated as the average value of the five spot analyses.

[0074] The analysis results, including the concentrations of Cr, Si and Al in the oxides on the surface of the steel material, and the concentrations of "Cr+Si", "Cr+Al" and "Cr+Si+Al", are shown in Table 2. "Cr+Si" indicates the sum of the Cr concentration and the Si concentration, while "Cr+Al" indicates the sum of the Cr concentration and the Al concentration. "Cr+Si+Al" indicates the sum of the Cr concentration, the Si concentration and the Al concentration.

[0075] If the "Cr+Si+Al" concentration was within the range of 5.0-12.0 mass%, it was evaluated as ○ (good), and if it was not within the range, it was evaluated as × (bad). Note that all steels that were evaluated as having a good result for "Cr+Si+Al" also satisfied the range of 4.0-12.0 mass% for at least either "Cr+Si" or "Cr+Al".

[0076] <Evaluation of oxidation gain> The red scale resistance of each steel material was evaluated based on the oxidation mass increase after an oxidation test in accordance with JIS Z2281. A test piece measuring 20 mm x 25 mm was cut from each steel material, and only the end face of the test piece was dry polished with a #600 abrasive. The test piece was continuously heated at 800°C for 100 hours in a nitrogen atmosphere containing 20% ​​water vapor, after which the oxidation mass increase (mg / cm 2 ) was measured.

[0077] The oxidation test was carried out twice for each steel material, and the average oxidation mass gain was calculated. The calculated oxidation mass gains are shown in Table 2. Regarding red scale resistance, the oxidation mass gain was 0.3 mg / cm 2 Less than 0.3mg / cm 2 The above was evaluated as × (bad).

[0078] <Weldability evaluation> The weldability of each steel material was evaluated based on the total crack length after arc strike welding. The test pieces used for evaluation were obtained by cutting 50 mm squares from each steel material with a plate thickness of 2 mm. Arc strike welding was performed with a TIG welding machine at a current of 120 A for 3 seconds, with Ar shielding gas at 10 mL / min, a φ2.4 mm electrode with a protrusion length of 5 mm, and an arc length of 1 mm. The susceptibility of each steel material to hot welding cracking was evaluated based on the presence or absence of cracks in the test pieces and the total crack length (mm). Table 2 shows the measurement results of the total crack length as the evaluation result of weldability. Regarding weldability, a total crack length of less than 5 mm was evaluated as ○ (good), and a total crack length of 5 mm or more was evaluated as × (poor).

[0079] <Result> Table 2 shows the overall evaluation results, with a rating of ○ (good) for each steel material when the element concentration of the oxide of the present invention on the surface, the oxidation weight gain, and the weldability were all evaluated as good, and a rating of × (bad) for when at least one of them was evaluated as poor.

[0080] As shown in Table 2, all of the steel materials produced using steel types A1 to A9 having the composition of the present invention and with a hydrofluoric acid concentration in the nitric hydrofluoric acid immersion step S9 in the range of 10 to 15 g / L had a specified element concentration of the oxide of the present invention on the surface of 4.0 to 12.0 mass%. The specified element concentration refers to the sum of the Cr concentration and the Al concentration and / or the Si concentration. Furthermore, all of these steel materials according to the invention examples had good red scale resistance and weldability.

[0081] On the other hand, the steel materials using the steel types A1 to A9, which were produced by setting the hydrofluoric acid concentration in the nitric hydrofluoric acid immersion step S9 to 5 g / L or 7.5 g / L, all had a specified element concentration of the oxide of the present invention on the surface exceeding 12.0 mass%. The steel materials according to these comparative examples were evaluated as having poor oxidation weight gain and weldability.

[0082] Moreover, all of the steel materials produced using the steel types B1 to B5 having compositions outside the composition of the present invention were evaluated as being poor in at least one of the oxidation weight gain and the weldability.

[0083] [Additional Notes] The present invention is not limited to the above-described embodiments or examples, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in the different embodiments and examples are also included in the technical scope of the present invention.

Claims

1. An austenitic stainless steel containing, by mass%, C: 0.12% or less, Si: 0.20 to 4.0%, Mn: 0.05 to 2.5%, P: 0.05% or less, S: 0.005% or less, Ni: 8.0 to 17.0%, Cr: 15 to 25.0%, Cu: 2.5% or less, Al: 0.01 to 1.0%, N: 0.35% or less, Mo: 3.0% or less, Nb: 0.8% or less, and Ti: 1.0% or less, with the balance being Fe and unavoidable impurities, An oxide containing Cr, Si and Al and having a major axis of 0.1 to 5 μm is formed on the surface, In the oxide, the total of the concentration of Cr and the concentration of at least one of Si and Al is 4.0 to 12.0 mass %, In the oxide, the total of a Cr concentration, a Si concentration, and an Al concentration is 5.0 to 12.0 mass %, According to JIS Z2281, a test piece of 20 mm x 25 mm was cut out from the austenitic stainless steel, and only the end surface of the test piece was dry-polished with a #600 abrasive. The test piece was continuously heated at 800°C for 100 hours in a nitrogen atmosphere containing 20% ​​water vapor, and the measured oxidation weight gain was 0.3 mg / cm. 2 Less than 100%. Austenitic stainless steel.

2. 2. The austenitic stainless steel according to claim 1, further containing, by mass%, one or more of B: 0.01% or less, Ca: 0.0002 to 0.0050%, Hf: 0.001 to 0.50%, Zr: 0.01 to 0.50%, Sb: 0.005 to 0.50%, Co: 0.01 to 1.50%, W: 0.01 to 2.0%, Ta: 0.001 to 1.0%, Sn: 0.002 to 0.5%, Ga: 0.0002 to 0.30%, Mg: 0.0003 to 0.0050%, and rare earth elements: 0.001 to 0.20%.

Citation Information

Patent Citations

  • Austenitic stainless steel for alcohol-base fuel reformer

    JP2003160843A

  • Austenitic stainless steel strip and manufacturing method therefor

    JP2003328085A

  • Austenitic stainless steel superior in red scale resistance

    JP2004043903A

  • Nonmagnetic austenitic stainless steel sheet and method for producing nonmagnetic member

    JP2018109215A

  • Austenitic stainless steel and method for producing the same

    JP2020172694A